LEF1 supports metastatic brain colonization by regulating glutathione metabolism and increasing ROS resistance in breast cancer. Issue 11 (11th November 2019) - Blazquez, Raquel; Rietkötter, Eva; Wenske, Britta; Wlochowitz, Darius; Sparrer, Daniela; Vollmer, Elena; Müller, Gunnar; Seegerer, Julia; Sun, Xueni; Dettmer, Katja; Barrantes‐Freer, Alonso; Stange, Lena; et al.
Abstract : More than half of all brain metastases show infiltrating rather than displacing growth at the macro‐metastasis/organ parenchyma interface (MMPI), a finding associated with shorter survival. The lymphoid enhancer‐binding factor‐1 (LEF1) is an epithelial‐mesenchymal transition (EMT) transcription factor that is commonly overexpressed in brain‐colonizing cancer cells. Here, we overexpressed LEF1 in an in vivo breast cancer brain colonization model. It shortened survival, albeit without engaging EMT at the MMPI. By differential proteome analysis, we identified a novel function of LEF1 as a regulator of the glutathione (GSH) system, the principal cellular redox buffer. LEF1 overexpression also conferred resistance against therapeutic GSH depletion during brain colonization and improved management of intracellular ROS. We conclude that besides EMT, LEF1 facilitates metastasis by improving the antioxidative capacity of epithelial breast cancer cells, in particular during colonization of the brain parenchyma. Abstract : What's new? More than half of all brain metastases show infiltrating rather than displacing growth at the macro‐metastasis/organ parenchyma interface (MMPI), a finding associated with shorter survival. LEF1 is an epithelial‐mesenchymal transition (EMT) transcription factor commonly overexpressed in brain‐colonizing breast cancer cells. Its role in infiltrative MMPIs remains unclear, however. This study identifies LEF1 as a critical regulator of glutathione metabolism aside from its EMT inducer role. LEF1 overexpression induces resistance against glutathione depletion and improves the antioxidative capacity of breast cancer cells. Increased glutathione fitness and reactive oxygen species resistance appear to be more relevant than EMT induction during brain colonization.